Consumers' perceptions of halal food certification - Norazah Mohd Suki; Norbayah Mohd Suki; Loi, Chek Kim (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2018)
Halal has been used as a benchmark for safety, hygiene and and product quality assurance.Empirical research into halal food certification is minimal. Hance, the goal of this research is to discribe selected aspects of respondent's perception of halal food certification. The descriptive statistics of the 20 factor item revealed that a significant number of respondents have a positive perception of halal food certification. they mainly expressed that halal food products are important to them. What's more,using halal food products is their own choice. Indeed, they have high inclination to choose halal food products over other types of products. Firms should play a dominant role in improving consumers' attitudes towards halal food certification in the challenging digital marketplace. Future research direction is also presented.